2019
DOI: 10.1007/s00404-019-05385-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of risk factors for breech presentation in preterm and term labor: a nationwide, population-based case–control study

Abstract: Purpose To determine if the common risks for breech presentation at term labor are also eligible in preterm labor. Methods A Finnish cross-sectional study included 737,788 singleton births (24-42 gestational weeks) during 2004-2014. A multivariable logistic regression analysis was used to calculate the risks of breech presentation. Results The incidence of breech presentation at delivery decreased from 23.5% in pregnancy weeks 24-27 to 2.5% in term pregnancies. In gestational weeks 24-27, preterm premature rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 43 publications
2
24
0
6
Order By: Relevance
“…We evaluated potential confounders, which could have an effect on the maternal and neonatal outcomes during the second delivery. We reviewed the following factors: maternal age below 25 and over 35 years, smoking, body mass index (BMI) ≥ 30 and ≥ 35, hypo-or hyperthyroidism, gestational diabetes and pre-existing type 1 diabetes mellitus, preeclampsia, placenta praevia, placental abruption, premature rupture of membranes (PROM), oligohydramnios congenital fetal anomalies, infant sex, and small for gestational age (SGA) according to Finnish standards [14,15].…”
Section: Populationmentioning
confidence: 99%
“…We evaluated potential confounders, which could have an effect on the maternal and neonatal outcomes during the second delivery. We reviewed the following factors: maternal age below 25 and over 35 years, smoking, body mass index (BMI) ≥ 30 and ≥ 35, hypo-or hyperthyroidism, gestational diabetes and pre-existing type 1 diabetes mellitus, preeclampsia, placenta praevia, placental abruption, premature rupture of membranes (PROM), oligohydramnios congenital fetal anomalies, infant sex, and small for gestational age (SGA) according to Finnish standards [14,15].…”
Section: Populationmentioning
confidence: 99%
“…The present results showed that women with a history of preterm birth exhibited 1.66 times higher risk of having PPH than those without a history of preterm birth. The reason may be that women with preterm deliveries often have pregnancy complications such as placenta previa and premature rupture of membranes, which cause endometrial damage and increase the risk of bleeding [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of gestational diabetes (11.5%) and gestational hypertension (9.9%) in this study were almost similar to the institutional incidence during the period which was 13.5% and 10.4% respectively. 27 In breech presentation as per se there is no increased incidence of medical complications.…”
Section: Discussionmentioning
confidence: 99%